Host-derived chimeric peptides clear the causative bacteria and augment host innate immunity during infection: A case study of HLB in citrus and fire blight in apple - Basu, Supratim; Sineva, Elena; Nguyen, Liza; Sikdar, Narattam; Park, Jong Won; Sinev, Mikhail; Kunta, Madhurababu; Gupta, Goutam (Frontiers in Plant Science, 2022)
Bacterial diseases cause severe losses in production and revenue of many fruit crops including citrus and apple. Huanglongbing (HLB) in citrus and fire blight in apple are two deadly diseases without any cure. Here, we introduce a novel therapy of HLB and fire blight by enhancing the innate immunity of the host plant. Specifically, we construct in silico a library of chimeras containing two different host peptides with observed or predicted antibacterial activity. Then, we perform bactericidal and toxicity tests in vitro to select a few non-toxic chimeras with high antibacterial activity. Finally, we conduct ex planta studies to show not only do the chimeras clear the causative bacteria from citrus leaves with HLB and from apple leaves with fire blight, but also, they augment host innate immunity during infection. The strategy described here can be extended to design host derived chimeras against multiple pathogenic bacteria that cause diseases in crop and fruit plants of agricultural importance.